The global impact of the Great Depression, 1929-1939 - Rothermund, Dietmar (Routledge, 1996)
Dietmar Rothermund broadens the conventional focus of the great depression to include its impact on the countries of Africa, Asia and Latin America. He explains key areas, such as Keynesian theory and the role of the international gold standard
Includes bibliographical references (p. 164-175) and index
Keywords: 1929-1939; Developing countries -- Economic conditions; Auswirkung; Weltwirtschaftskrise